A novel two-component system contributing the catabolism of c-di-GMP influences virulence in Aeromonas veronii - Liu, Chaolun; Shao, Jia; Ma, Xiang; Tang, Yanqiong; Li, Juanjuan; Li, Hong; Chi, Xue; Liu, Zhu (Frontiers in Microbiology, 2025)
IntroductionResponse regulators from diverse two-component systems often function as diguanylate cyclases or phosphodiesterases, thereby enabling precise regulation of intracellular c-di-GMP levels to control bacterial virulence and motility. However, the regulatory mechanisms of c-di-GMP require further elucidation.MethodsThis study confirmed that ArrS and ArrR form a two-component system via structural analysis, two-hybrid, and phosphodiesterase activity detection. To evaluate the impact of ArrS/ArrR on intracellular c-di-GMP levels, biofilm detection, motility detection, fluorescence reporter plasmids, and LC-MS/MS analysis were employed. One-hybrid, EMSA, and RT-qPCR were used to demonstrate the function of ArgR on arrSR promoter. The roles of ArrS/ArrR in Aeromonas veronii were investigated using RT-qPCR, murine model, and proteomics.ResultsArrS and ArrR constituted a two-component system in Aeromonas veronii and were transcriptionally repressed by ArgR. ArrR exhibited phosphodiesterase activity, which is inhibited through phosphorylation mediated by ArrS. In Aeromonas veronii, ArrS/ArrR significantly altered the intracellular c-di-GMP levels. In a murine model, ΔarrS exhibited increased pathogenicity, leading to elevated TNF-α and IFN-γ levels in serum, and severer toxicity to spleen and kidney. These effects might be elucidated by the upregulated inflammation-associated proteins in ΔarrS. Moreover, the exonuclease RecB was also up-regulated in ΔarrS.DiscussionWe elucidated the regulatory mechanism of ArrS/ArrR on intracellular c-di-GMP levels and its impact on the virulence in Aeromonas veronii, and discussed the intricate relationship between c-di-GMP metabolism and arginine metabolism.